Multimedia guide: Pedagogical strategy to educate about Extracorporeal Circulation Therapy - Álvarez Idarraga, Nelly Johana; Mantilla Bermúdez, David Enrique (Rastros Rostros, 2023)
Objective: To promote the understanding of Extracorporeal Circulation Therapy in relatives of patients undergoing this process, through the design of a multimedia guide. Materials and methods: A phenomenological qualitative study with a semi-structured interview technique, in which 4 ecmologist nurses and 22 relatives of patients participated. The pre and post interviews were recorded and transcribed. A web page was designed for the relatives of the patients in Extracorporeal Circulation Therapy. Results: After implementing the multimedia guide, the nurses reported that the relatives of patients undergoing Extracorporeal Circulation Therapy decreased their level of anxiety and worry; revealed greater autonomy in decision-making, cleared up their doubts, and the workload of the ecmologist nurses decreased. Conclusions: Providing educational tools aimed at relatives of patients in Extracorporeal Circulation Therapy decreases the level of anxiety of relatives and favors their participation in the recovery of patients